Methanolic extract of Abrus precatorius promotes breast cancer MDA-MB-231 cell death by inducing cell cycle arrest at G0/G1 and upregulating Bax - Ismail, Norzila; Ibrahim, Wan Suriyani Wan; Salleh, Siti Farhanah Mohd; Yajid, Aidy Irman; Wong, Michael Pak-Kai; Hashim, Mohd Nizam Md (Elsevier, 2019)
Objective: To determine the anti-proliferative activity of Abrus precatorius (A. precatorius) leaf extracts and their effect on cell death. Methods: A. precatorius leaves were extracted successively with hexane, ethyl acetate and methanol by Soxhlet extraction. Aqueous extract was prepared by decoction at 50. Extracts of A. precatorius leaves were used to treat selected cancer and normal cell lines for 72 h. Furthermore, 3-(4,5-dimethyl thiazol-2-yl) 2,5-diphenyl tetrazolium bromide assay was performed to determine cell viability. Analysis of cell cycle arrest, apoptosis assay and apoptosis protein expressions were determined by flow cytometry. Results: Methanolic extract of A. precatorius leaves showed the lowest IC50 on MDA-MB-231 cells at (26.40依5.40) μg/mL. Flow cytometry analysis revealed that cell arrest occurred at G0/ G1 phase and the apoptosis assay showed the occurrence of early apoptosis at 48 h in MDAMB- 231 cells treated with methanolic extract of A. precatorius leaves. Methanolic extract of A. precatorius leaves induced apoptosis by upregulation of Bax, p53 and caspase-3 and downregulation of Bcl-2. Conclusions: Methanolic extract of A. precatorius leaves promotes MDA-MB-231 cell death by inducing cell cycle arrest and apoptosis possibly via the mitochondrial-related pathway.